2015
DOI: 10.1371/journal.ppat.1005055
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Evolving Genes Are Key Players in Host Specialization and Virulence of the Fungal Wheat Pathogen Zymoseptoria tritici (Mycosphaerella graminicola)

Abstract: The speciation of pathogens can be driven by divergent host specialization. Specialization to a new host is possible via the acquisition of advantageous mutations fixed by positive selection. Comparative genome analyses of closely related species allows for the identification of such key substitutions via inference of genome-wide signatures of positive selection. We previously used a comparative genomics framework to identify genes that have evolved under positive selection during speciation of the prominent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…Two highly conserved lysin motif (LysM) effectors, Mg1LysM and Mg3LysM, prevent fungal recognition and shield the fungal cell wall from degradation by host hydrolytic enzymes (Marshall et al ., 2011). The other known effectors of Z. tritici , Zt80707, AvrStb6 and Zt_8_609, are rapidly evolving small secreted proteins (Poppe et al ., 2015; Hartmann et al ., 2017; Zhong et al ., 2017; Kema et al ., 2018). The latter two were identified because they are specifically recognised by certain wheat cultivars, and they were found to be located in transposable element‐rich genomic regions (Brading et al ., 2002; Hartmann et al ., 2017; Zhong et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two highly conserved lysin motif (LysM) effectors, Mg1LysM and Mg3LysM, prevent fungal recognition and shield the fungal cell wall from degradation by host hydrolytic enzymes (Marshall et al ., 2011). The other known effectors of Z. tritici , Zt80707, AvrStb6 and Zt_8_609, are rapidly evolving small secreted proteins (Poppe et al ., 2015; Hartmann et al ., 2017; Zhong et al ., 2017; Kema et al ., 2018). The latter two were identified because they are specifically recognised by certain wheat cultivars, and they were found to be located in transposable element‐rich genomic regions (Brading et al ., 2002; Hartmann et al ., 2017; Zhong et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the genome and transcriptome of Z. tritici revealed a large number of putative effector genes encoding small secreted proteins (SSPs) that are likely involved in virulence (32, 33). Genes encoding SSPs evolved more rapidly than the genomic background (25, 34) and were more likely to lack orthologs in closely related species (33). Genomic analyses suggested that numerous genes (including effector genes) were deleted in at least some isolates of the species (31, 35).…”
Section: Introductionmentioning
confidence: 99%
“…However, although it is important to elucidate the origin and maintenance of variations in pathogen fitness on different hosts for developing durable means of controlling disease, most current understanding is still largely based on theoretical predictions (Brown and Tellier, 2011; Laine and Tellier, 2008; Schulze-Lefert and Panstruga, 2011; Thrall et al, 2015). Thus there is a lack of studies investigating the molecular or physiological bases of variation in pathogen fitness across pathogen populations, especially in fungi (Poppe et al, 2015). …”
Section: Introductionmentioning
confidence: 99%